Object-Oriented Modeling of Matching to Systemic Classifiers - Sedrak V. Grigoryan; Nairi P. Hakobyan; Hovhannes S. Vrtanesyan (Изд-во НАН РА)
In this paper we present a version of object-oriented implementation of models of constructive regularized mental systems, mentals, and systemic classifiers introduced in [1] as well as algorithms for matching them to situations. We experiment the adequacy of the models and algorithms for the chess representing kernels of the class of combinatorial problems, where space of solutions can be represented by Reproducible Game Trees (RGT).
Keywords: Mathematics; Computer software